2013
DOI: 10.4172/2329-9002.1000108
|View full text |Cite
|
Sign up to set email alerts
|

Computational Phylogenetic Study and Data Mining Approach to Laccase Enzyme Sequences

Abstract: Currently data mining is an essential tool to discover the hidden data and important patterns from a large data set. The present work is a pilot study that compares the result of sequence based phylogenetic study and some of the physicochemical and structural feature based clustering of Laccase enzyme sequences. Total of 50 homologous sequences were obtained specific to each of the organism like plant, fungi and bacteria. Multiple sequences alignment of sequences was performed followed by phylogenetic tree con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…3). The fifty specific laccase gene sequences from different organisms including fungi were compared by multiple sequence alignment and results of the phylogenetic analysis reported diversity of the derived proteins (Satpathy et al, 2013). The protein coding genes have been used to study the phylogenetic analysis among Ascomycetes and Zygomycetes fungi as reported earlier by several coworkers (Diezmann et al, 2004;Tanabe et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…3). The fifty specific laccase gene sequences from different organisms including fungi were compared by multiple sequence alignment and results of the phylogenetic analysis reported diversity of the derived proteins (Satpathy et al, 2013). The protein coding genes have been used to study the phylogenetic analysis among Ascomycetes and Zygomycetes fungi as reported earlier by several coworkers (Diezmann et al, 2004;Tanabe et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…The complete alignment of these sequences with a Clustal-X instrument was combined using the MEGA X software. The phylogenetic tree showed a taxonomic clustering through the major taxa (Satpathy 2014). The neighboring relationship of sequences was demonstrated by constructing a phylogenetic tree (Figure 4).…”
Section: Phylogenetic Analysismentioning
confidence: 99%
“…The distance matrix of the suitable clustering system is used to create the phylogenetic tree. Mostly, phylogenetic analysis of enzyme sequences is a powerful instrument for group and interpretation of the taxa (Satpathy 2014). Surely, phylogenetic tree interpretation is constructed for most of the comparative evolutionary biology.…”
Section: Introductionmentioning
confidence: 99%